Jasmonate-Related MYC Transcription Factors Are Functionally Conserved in Marchantia polymorpha. Issue 10 (7th August 2019) - Peñuelas, María; Monte, Isabel; Schweizer, Fabian; Vallat, Armelle; Reymond, Philippe; García-Casado, Gloria; Franco-Zorrilla, Jose M.; Solano, Roberto
Abstract : Despite 450 million years of independent evolution, MYC transcription factors that regulate jasmonate responses are functionally conserved between bryophytes and eudicots. Abstract: The lipid-derived phytohormone jasmonoyl-isoleucine regulates plant immunity, growth and development in vascular plants by activating genome-wide transcriptional reprogramming. In Arabidopsis ( Arabidopsis thaliana ), this process is largely orchestrated by the master regulator MYC2 and related transcription factors (TFs). However, the TFs activating this pathway in basal plant lineages are currently unknown. We report the functional conservation of MYC-related TFs between the eudicot Arabidopsis and the liverwort Marchantia polymorpha, a plant belonging to an early diverging lineage of land plants. Phylogenetic analysis suggests that MYC function first appeared in charophycean algae and therefore predates the evolutionary appearance of any other jasmonate pathway component. M. polymorpha possesses two functionally interchangeable MYC genes, one in females and one in males. Similar to AtMYC2, MpMYCs showed nuclear localization, interaction with JASMONATE-ZIM-DOMAIN PROTEIN repressors, and regulation by light. Phenotypic and molecular characterization of loss- and gain-of-function mutants demonstrated that MpMYCs are necessary and sufficient for activating the jasmonate pathway in M. polymorpha, but unlike their Arabidopsis orthologs, do not regulate fertility. Therefore, despite 450 million years of independent evolution, MYCs are functionally conserved between bryophytes and eudicots. Genetic conservation in an early diverging lineage suggests that MYC function existed in the common ancestor of land plants and evolved from a preexisting MYC function in charophycean algae.